Career development in civil service: issues for discussion - Sinha, Dharni P
Here this paper attempts to raise some issues on career development aspect of the Civil Service. According to author career development has to be a joint effort of the civil servant and the government, neither can help to achieve it unilaterally. To the government, career planning, of civil servants helps it to build suitable managerial manpower for deployment to meet its administrative needs. There are several measures which will support the objectives of career development in public service. (a). Systematic Manpower Planning and Recruitment; (b). Balanced Experience Building Assignment and postings; (c). Effective Performance Appraisal, Feedback, Counselling and Promotion System and (d). Appropriate Trai
Keywords: Nepal Administrative College; Public Service Commissions; Professionalism; Career Service; Civil Service - Nepal